An unprecedented single platform via cross-linking of zeolite and MOFs. Issue 41 (18th April 2016) - Lim, Dae-Woon; Lee, Heeju; Kim, Sungjune; Cho, In Hwa; Yoon, Minyoung; Choi, Yong Nam
Abstract : The unprecedented ternary nanocomposites have been synthesized as a single platform via cross-linking of two nanoporous materials, MOFs and Pt nanoparticle (NP) loaded zeolite. Abstract : The unprecedented ternary nanocomposites have been synthesized as a single platform via cross-linking of two nanoporous materials, MOFs and Pt nanoparticle (NP) loaded zeolite. The heterojunction of the novel nanocomposites is anticipated to work as a chemical platform for size selective catalytic hydrogenation or deuteration of small molecules.